PRIMARY SCHOOL TEACHER TRAINING IN BRAZIL: A PROPOSAL WHICH CONTEMPLATES THE PARADIGM OF COMPLEXITY IN THE TRANSDISCIPLINARY VISION - F. L. de, Oliveira,; M. A., Behrens (European Scientific Journal, ESJ, 2015)
This article originates from part of a research, with a focus on the issue: How to offer a proper in-service continuous training programme which contemplates the Paradigm of Complexity, catering for a transdisciplinary vision, in the search of the (re)construction and consolidation of the pedagogical knowledge of teachers who work with early childhood education? This research, of a descriptive nature, is linked to the group called PEFOP - Paradigmas Educacionais Formação de Professores, allocated to the stricto sensu Graduate Programme in Education, at Pontifícia Universidade Católica do Paraná-Brazil. The research as a whole aims to investigate the point of view of teachers who work with early childhood education, proposing the curricular extension in regards to teacher training, emphasizing the importance of the complexity vision in the pedagogical practice. It proposes the investigation of different professional training possibilities of this level of education, taking into account the necessity of a pragmatic change to teaching practice. In this article which was consolidated while the researcher sought to understand the components that make up the change of early childhood education professionals. The investigation allowed us to realize that the professionals who work with this level of education can enhance their teaching practice, having as basis the transdisciplinary vision, focusing on the paradigmatic change of the Complexity. This, as a comprehensive theoretical-practical basis, allows a methodological unleashing able to build substrates to go beyond the content included in the curriculum, in search of learning which is really significant to the lives of the students.